A Porous Stone Technique to Measure the Initial Water Uptake by Supplementary Cementitious Materials - Andras Fehervari (MDPI AG, 2021)
The decades-long use of supplementary cementitious materials (SCMs) as replacements for ordinary Portland cement (OPC) by the cement and concrete industry is undergoing a resurgence in research activities related to goals addressing circular economy activities, as well as reduction in CO2 emissions. Differences in the chemistry, mineralogy and reactivity of SCMs compared to OPC impact the fresh properties of concrete. Some SCMs exhibit greater initial water uptake and thus compete strongly with OPC for water during hydration. This study focuses on the early interaction with water as a primary factor that determines the resulting fresh properties and workability. Currently, no test (standard or otherwise) is available for quantifying initial interactions between water and cementitious materials. A quick and reliable method to measure the initial water uptake of SCMs is presented herein, which relies on their affinity to water. The method enables the calculation of water-to-binder ratios for different SCMs required to achieve the same workability as a reference OPC. The results are then well correlated to measured slump and bleed properties. We propose this simple technique to be used by researchers and industry practitioners to better predict the fresh properties of concretes, mortars, or pastes with SCMs.